Towards a new stakeholder-inclusive conceptual framework to strengthen internal corporate image - Yolandi Slabbert (Communicare)
It is widely reported in the literature that employees’ image of the organisation has a direct influence on external stakeholders’ image of the organisation. This research attempted to address the need for an approach that facilitates employee engagement coupled with a leadership approach that allows collaboration, inclusion and co-operation within the organisation, to strengthen the internal corporate image. A synthesis of the literature from a unique stakeholder-inclusive perspective, depicted in the King III Report on corporate governance, was conducted to identify the theoretical principles for a preliminary conceptual framework explored through a case study approach. Parsec Technologies Pty Ltd was purposively selected as case study, because it was the 2012 and 2013 winner in the manufacturing sector of the Deloitte Best Company to Work For (BCTWF) survey, and served as a best practice organisation in the context of this research. Data triangulation by means of one-on-one interviews, focus groups and an open-ended survey was conducted with employees to determine the pragmatic relevance of the proposed framework. The findings culminated in a new generic stakeholder-inclusive conceptual framework to strengthen the internal corporate image by means of the AA1000 Stakeholder Engagement Standard elements and responsible leadership. Although a single case study is limited, this framework contributed to the body of knowledge on corporate image to provide organisations with guidelines for strengthening their internal corporate image.